If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying A + 3 = b Reorder the terms: 3 + A = b Solving 3 + A = b Solving for variable 'A'. Move all terms containing A to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + A = -3 + b Combine like terms: 3 + -3 = 0 0 + A = -3 + b A = -3 + b Simplifying A = -3 + b
| 7x+4=-x+-10 | | k+3.91=287 | | 4Y-8=3Y-4 | | 5x^4-3x^2=0 | | 22-7=3a | | 12.45=g+4g | | 1.21=5z+6z | | -61-7=17 | | 125=13c+12c | | 6x+9=-9+8x | | 5x+37=8x-8 | | c+20c=105 | | 5n+n+6+11= | | 8x+4=3x+14 | | 6x+11=54-7x | | -17-4x=10x+21 | | 4*2+3*x=11 | | 5a=-5a+17 | | k^2+4k+20=0 | | 1500+.15p=2430 | | x^3+6x^2-3x-22=0 | | x^3+6x^2-3x+22=0 | | 7p-2=9p+b | | y=-1.36x^2+27.8x+77 | | x^3+6x^2-3x=-10 | | x^3+6x^2-3x+10=0 | | x^3+6x^2-3x+10= | | f(x)=-1.36x^2+27.8x+77 | | 2*x-8=2 | | 3(3x+2)=34-x | | 7x-6-(x+2)=4x-2*3 | | x^3-6x^2-3x+10=0 |